Informal Learning through Religious Social Activities in the Community as the Internalization of Religious Values in Adolescents - Safitri, Diah; Dayanti, Umi; Zulkarnain, Zulkarnain (Proceedings Series of Educational Studies, 2024)
Religious social activities are forms of activities related to religion. These activities balance scientific knowledge with religious knowledge. The purpose of this research is to understand informal learning through religious social activities as a means of internalizing religious values in adolescents, as well as to assess the support from families. This research employs qualitative methods with a case study approach. The findings indicate that the religious social activities participated in by adolescents are organized by the community and mosque youth organizations. The internalization of religious values in adolescents through informal learning is incorporated into various activities such as habituation, advice-giving, and sermons. In this internalization process, several small changes have begun to be implemented by adolescents in their daily lives. Additionally, adolescents receive full support from their families in these religious social activities, which further motivates them to deepen their religious knowledge.